1996
DOI: 10.1021/ef950066t
|View full text |Cite
|
Sign up to set email alerts
|

NO Reduction by Activated Carbons. 7. Some Mechanistic Aspects of Uncatalyzed and Catalyzed Reaction

Abstract: In this last paper of a series devoted to uncatalyzed and catalyzed reduction of NO by carbon, we discuss some mechanistic aspects of this reaction, which is thought to be a viable alternative to selective catalytic reduction by ammonia or hydrocarbons. We present a summary of the results of isothermal and temperature-programmed reduction studies on a metal-free activated carbon and carbon loaded with K, Ca, Fe, Cu, Cr, Co, and Ni catalysts. All the results obtained on catalyzed NO reduction are consistent wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
106
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(116 citation statements)
references
References 111 publications
9
106
0
1
Order By: Relevance
“…Moreover a deeper knowledge of the chemistry involved in the formation and the reduction of NO X is required. Many authors have performed NO heterogeneous reduction studies on carbonaceous materials using, mainly, chars from phenol-formaldehyde resins [4][5][6][7][8][9], graphites [10] and activated carbons [11][12][13]. The use of model compounds, with controlled heteroatom content and well defined functionalities, is a useful approach that has been used by other authors [14,15] to study the release of nitrogen compounds from char combustion.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover a deeper knowledge of the chemistry involved in the formation and the reduction of NO X is required. Many authors have performed NO heterogeneous reduction studies on carbonaceous materials using, mainly, chars from phenol-formaldehyde resins [4][5][6][7][8][9], graphites [10] and activated carbons [11][12][13]. The use of model compounds, with controlled heteroatom content and well defined functionalities, is a useful approach that has been used by other authors [14,15] to study the release of nitrogen compounds from char combustion.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1990's Illán-Gômez et al [17,18] reported that activated carbon is active in NO x reduction in a temperature window between 400 and 500 °C. A large fuel injection upstream of a catalyst bed might promote the carbon formation and this in turn might enhance the NO x reduction.…”
Section: Recently Bisaiji Et Al (Toyota Motormentioning
confidence: 99%
“…Using carbon as a reductant offers obvious advantages, these include: (1) soot is present in the exhaust gas or produced from injected fuel and (2) its oxygen scavenging capability 22 1. Introduction [43,44]. The NO reduction by activated carbons originating from different raw materials shows that the NO reduction begins in the temperature range from 250 to 400 ∘ C and exhibits a sharp increase up to 100% conversion above 650 ∘ C [45].…”
Section: No Reduction With Sootmentioning
confidence: 99%
“…The soot oxidation accelerated by the presence of NO [49]. Simultaneously, only up to 10-15% of NO is converted into N [43]. This method is regarded as a successful method to remove the soot, however, for NO reduction, this technology will be not able to meet any of the NO emission standards.…”
Section: Continuously Regenerating Trap (Crt)mentioning
confidence: 99%